2008
DOI: 10.1002/fld.1927
|View full text |Cite
|
Sign up to set email alerts
|

Robustness and accuracy of SPH formulations for viscous flow

Abstract: SUMMARYNumerous methods are available for the modelling of viscous stress terms in smoothed particle hydrodynamics (SPH). In this work, the existing methods are investigated systematically and evaluated for a range of Reynolds numbers using Poiseuille channel and lid-driven cavity test cases. The best results are obtained using two methods based on combinations of finite difference and SPH approximations, due to Morris et al. and Cleary. Gradients of high-valued functions are shown to be inaccurately estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 26 publications
4
69
0
Order By: Relevance
“…The sum includes the term k = j. Basa et al 12 showed that Eq. (11) is the best among different available schemes in smoothed particle hydrodynamics for approximation of the second derivatives.…”
Section: Viscous Dampingmentioning
confidence: 99%
“…The sum includes the term k = j. Basa et al 12 showed that Eq. (11) is the best among different available schemes in smoothed particle hydrodynamics for approximation of the second derivatives.…”
Section: Viscous Dampingmentioning
confidence: 99%
“…Therefore, this formulation conserves linear and angular momentum. These properties are discussed more fully by Violeau and Issa [9] and Basa et al [10]. The term R ab f ab ∇W ab is Monaghan's interparticle force [11] defined by…”
Section: Sph Discretisationmentioning
confidence: 99%
“…Similarly, at the outflow boundary, J 1 and J 2 should be determined from the interior, while the boundary condition is J 3 = 0. By inverting the system of equations (10)(11)(12), it is straightforward to express pressure, density, and velocity as functions of the characteristic variables as shown below.…”
Section: Non-reflecting Boundary Condi-tionsmentioning
confidence: 99%
“…The truncation errors of the SPH discretization of spatial derivatives have been studied numerically in [31,32] and analytically in [18,33]. In SPH, particles move with the fluid velocity and become disordered in the nonuniform velocity field.…”
Section: Error Analysis Of Sph Derivative Operators and Operator Corrmentioning
confidence: 99%